IMMUNOHISTOCHEMICAL PROPERTIES OF THE LIVER OF INFANTS WHO DIED IN THE NEONATAL PERIOD BORN WITH PREECLAMATION - Eshbaev E.A., Allanazarov I.M.; Yoldosheva D.S. (Central Asian Journal of Medicine, 2025)
In order to examine the changes in the liver of infants who died in the early neonatal period due to preeclampsia, immunohistochemistry was used to detect active changes in hepatocytes, to determine whether or not the characteristics of hepatocytes change, and to interpret the changes in the antigenic structure. It should be noted that through immunohistochemical examination, we were able to detect necrosis, pre-necrosis, proliferative indicators, and then to determine the activity of blood cells in the liver.